Tsunami deposits refine great earthquake rupture extent and recurrence over the past 1300 years along the Nankai and Tokai fault segments of the Nankai Trough, Japan. (1st January 2020) - Fujiwara, Osamu; Aoshima, Akira; Irizuki, Toshiaki; Ono, Eisuke; Obrochta, Stephen P.; Sampei, Yoshikazu; Sato, Yoshiki; Takahashi, Ayumi
Abstract: Study of prehistoric to medieval-age tsunami deposits along a riverbank site near the eastern Nankai Trough, central Japan, show that, not only did Tokai earthquakes occur with a higher frequency than previously thought, but that contemporaneous ruptures of the Tokai and Nankai fault segments were also more common. The site revealed a ∼1-km long coast-normal cross section of the strand plain and exposed four sandy tsunami deposits, each of which indicates inundation over 2 km inland of the coast. Radiocarbon dating of previously studied and newly discovered deposits in the region indicates a shorter recurrence time for Tokai earthquakes and clarifies their linkage with Nankai earthquakes. We attribute the younger two tsunami deposits to the 1498 and 1096 CE Tokai earthquakes. The older two deposits confirm the occurrence of the Tokai earthquakes in 887 CE and in the latest 7th century. These events are not reliably recorded in historical documents in the Tokai region but were noted in the Nankai area. The 887 CE earthquake likely represents a full-length rupture of the Tokai and Nankai segments, as was the case for the 1707 CE earthquake. Integrated with the previous studies, these new results show that nine Tokai earthquakes occurred over the last 1300 years, the oldest in the latest 7th century, and in 887, 1096, 1361, 1498, 1614, 1707, 1854 and 1944 CE. Recalculated recurrence intervals range from 90 to 265 years. Except for the 1498 Meio Tokai earthquake, the Tokai earthquakes occurred simultaneously with Nankai earthquakes. Highlights: A new recurrence model of Nankai Trough earthquakes derived from geological data. Nine Tokai earthquakes occurred over the last 1300 years. They occurred with a higher frequency than previously thought. With one exception, they occurred simultaneously with the Nankai earthquakes.